Influence of covering soybean seeds with bentonite clay on biometric parameters under different irrigation regimes. - Yodgorov Normumin Gulomovich; Tilovov Ural Khusanovich; Khasanov Bobur (Genius Journals, 2023)
In the bottom article, the effect of encapsulation of soybean seeds with bentonite clays in the amount of 30, 40 and 50 kg/t is shown . on the biometric indicators of the plant under different irrigation regimes.
Keywords: Bentonite; soybean; variety